An Examination of the State of Ministry of Food and Agriculture’s (MoFA) Public Relation Unit Handling of Fall Armyworm (FAW) Breakout in Ghana - Okam, Blessing J. (UniMAC - GIJ, 2020)
In 2016, the first report of Fall Armyworm (FAW) was announced in the Eastern region of Ghana although this larva dates to 1797 following destruction in Georgia (CABI, 2017). Spodoptera frugiperda (Fall Armyworm) is an insect native to the tropical and subtropical regions of the Americas (CABI, 2017). Fall armyworm (FAW) is the larvae life stage of fall armyworm moth known to cause significant damage to crop. In Ghana, FAW accounts for US$ 64 million loss resulting from crop damage (Ansah-Amprofi, 2018). To reduce this damage, a few communications have been established and led in Ghana by the Ministry of Food and Agriculture's Public Relations Unit (Ansah-Amprofi, 2018).
THESIS